Правовий режим державного кордону України у забезпеченні прикордонної безпеки - Бєлєвцева, В. В.; Белевцева, В. В.; Belevceva, V. (My University, 2013)
The article is sanctified to research of questions related to functioning of the regime of state boundary. Problems and blanks are educed in the legislation of Ukraine in the field of providing of boundary safety. In conclusions basic directions over of activity of legislator are brought in relation to the improvement of legal base on providing of boundary safety.
Бєлєвцева В. В. Правовий режим державного кордону України у забезпеченні прикордонної безпеки / В. В. Бєлєвцева // Актуальні проблеми політики : зб. наук. пр. / редкол. : С. В. Ківалов (голов. ред..), Л. І. Кормич (заст. голов. ред..), Ю. П. Аленін [та ін.] ; МОН України ; НУ ОЮА. – Одеса : Фенікс, 2013. – Вип. 48. – С. 389-397.
Keywords: функціонування режиму державного кордону; державний кордон України; законодавство України у сфері забезпечення прикордонної безпеки; функционирование режима государственной границы; государственная граница Украины; законодательство Украины в сфере обеспечения пограничной безопасности; the functioning of the state border; state border of Ukraine; Ukrainian legislation in the field of border security